Burden, pattern, and causes of road traffic accidents in South India: Estimate of years of life lost - Paramjot Panda; Vamsi Krishna Boyanagari; Ravishankar Ayyanar (Wolters Kluwer Medknow Publications, 2019)
Context: Road traffic accident (RTA) is one of the major preventable public health problems and is on the rise. Aims: The aims of this study were to estimate the burden of RTA in Andhra Pradesh calculating years of life lost (YLL) and age-standardized YLL rates and to evaluate sex- and age-related differences in premature mortality. Subjects and Materials: The data were obtained from State Crime Record Bureau of Andhra Pradesh and Census of India 2011 for age-specific population to calculate YLL and mortality rates were calculated based on the age of the person involved in the accident. Results: A total of 24,258 RTA cases were reported from January 2015 to December 2015. Most of the cases 16,995 reported RTA are from rural areas. The time slot with the highest rate of road accidents in the morning was 09:00 am-12:00 am and in the evening was 06:00 pm-09:00 pm. The age group 25-34 years were the most vulnerable toward road accidental death of which male and female died in RTA were 929 (26.57%) and 101 (28.06%), respectively. Most of the RTA occurred at T-Junctions causing 5548 accidents with a share of 31.52% the total RTA on Junctions, the total YLL was 89,557, and highest YLL was 25,486 in 25-34 years of age group. Conclusions: We conclude that there is high fatal mortality and YLL in young age group in Andhra Pradesh. These are preventable events, and efforts to reduce the associated economic and social burden must be made.